2023
DOI: 10.1111/pan.14740
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative recovery in preschool‐aged children: A secondary analysis of a randomized controlled trial comparing premedication with midazolam, clonidine, and dexmedetomidine

Abstract: BackgroundPreoperative anxiety in pediatric patients can worsen postoperative outcomes and delay discharge. Drugs aimed at reducing preoperative anxiety and facilitating postoperative recovery are available; however, their effects on postoperative recovery from propofol‐remifentanil anesthesia have not been studied in preschool‐aged children. Thus, we aimed to investigate the effects of three sedative premedications on postoperative recovery from total intravenous anesthesia in children aged 2–6 years.MethodsI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Preoperative nursing visit was reported to have similar effects [22]. However, recent studies indicated that preoperative medication of sedatives and non-pharmacological interventions could reduce anxiety and improve the quality of anesthesia recovery, but could not improve the postoperative recovery [23][24][25]. The different surgery type and evaluation scales might account for these differences.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative nursing visit was reported to have similar effects [22]. However, recent studies indicated that preoperative medication of sedatives and non-pharmacological interventions could reduce anxiety and improve the quality of anesthesia recovery, but could not improve the postoperative recovery [23][24][25]. The different surgery type and evaluation scales might account for these differences.…”
Section: Discussionmentioning
confidence: 99%